Synthesis of new cocrystal solid form of fluconazole-fumaric acid - Owoyemi, Bolaji Charles Dayo (2015)
Pharmaceutical cocrystals are multicomponent crystalline solids comprised of an active pharmaceutical ingredient (API) and one or more co-formers interacting through hydrogen bonding or other weak interactions like the π-stack and van der Waals interactions. Fluconazole (FLZ) is a triazole antifungal drug used in the treatment and prevention of superficial and systemic fungal infections. It is also used to prevent and treat meningitis. Cocrystallization is an alternative approach for enhancement of drug. It can be performed using neat grinding, solvent assisted grinding, solvent evaporation, cooling evaporation and slurry cocrystallization. In this work, a new cocrystal Fluconazol-Fumaric acid monohydrate was synthesized via 1:1 stoichiometric amount of FLZ and FUM at different conditions. The characterization of the synthesized cocrystals was achieved using Raman spectroscopy, differential scanning calorimetry, powder X-ray diffraction and single crystal X-ray diffraction. The results obtained for the characterization of the samples showed some obvious differences among the spectra, diffractograms and thermograms. The single crystal X-ray diffraction analysis of the new structure shows a cocrystal where the fluconazole molecules are attached to the fumaric acid and water molecules respectively through hydrogen bonds, gave unique cell dimensions for an assumed structure C17H18F2N6O6 with a space group of P21/n, a = 17.053(3) Å, b = 5.5995(10), c=21.154(3), α = 90°, β=105.418(4)°, γ= 90°, V = 1947.3(6) Å3. This work is the first to report a monohydrate cocrystal structure of fluconazole and fumaric acid.